Glycogen synthase kinase 3 beta: can it be a target for oral cancer - Mishra, Rajakishore (BioMed Central, 2010)
Despite progress in treatment approaches for oral cancer, there has been only modest improvement in patient outcomes in the past three decades. The frequent treatment failure is due to the failure to control tumor recurrence and metastasis. These failures suggest that new targets should be identified to reverse oral epithelial dysplastic lesions. Recent developments suggest an active role of glycogen synthase kinase 3 beta (GSK3 β) in various human cancers either as a tumor suppressor or as a tumor promoter. GSK3β is a Ser/Thr protein kinase, and there is emerging evidence that it is a tumor suppressor in oral cancer. The evidence suggests a link between key players in oral cancer that control transcription, accelerated cell cycle progression, activation of invasion/metastasis and anti-apoptosis, and regulation of these factors by GSK3β. Moreover, the major upstream kinases of GSK3β and their oncogenic activation by several etiological agents of oral cancer support this hypothesis. In spite of all this evidence, a detailed analysis of the role of GSK3β in oral cancer and of its therapeutic potential has yet to be conducted by the scientific community. The focus of this review is to discuss the multitude of roles of GSK3β, its possible role in controlling different oncogenic events and how it can be targeted in oral cancer.